Fiscal Decentralization, Government Performance on Regional Government Financial Reporting Accountability - Sema Millenium Dua Ribu; Nurdiono Nurdiono; Reni Oktavia (Cita konsultindo, 2024)
This research aims to test the effect of Fiscal Decentralization and Government Performance on Regional Government Financial Reporting Accountability. This research is a literature review research. The literature review used is the latest journal that is no more than 10 years old. The research results show that Fiscal Decentralization and Government Performance have a positive and significant effect on the Accountability of Regional Government Financial Reporting.